In the company of cheerful ladies - McCall Smith, Alexander, 1948- (New York : Pantheon Books, 2004)
Handling a busy case load at The No. 1 Ladies' Detective Agency and contending with an intruder in her home, Mma Ramotswe has plenty on her mind. So when her unfortunate past returns to haunt her, she is happy her husband, Mr. J.L.B. Matekoni, is distracted as well. It seems one of his apprentices at Tlokweng Road Speedy Motors has raced off with an older, wealthy woman.
Keywords: No. 1 Ladies' Detective Agency (Imaginary organization) -- Fiction; Ramotswe, Precious (Fictitious character) -- Fiction; Women private investigators -- Botswana -- Fiction; Botswana -- Fiction